2018
DOI: 10.1371/journal.pone.0193412
|View full text |Cite
|
Sign up to set email alerts
|

The first in vivo multiparametric comparison of different radiation exposure biomarkers in human blood

Abstract: The increasing risk of acute large-scale radiological/nuclear exposures of population underlines the necessity of developing new, rapid and high throughput biodosimetric tools for estimation of received dose and initial triage. We aimed to compare the induction and persistence of different radiation exposure biomarkers in human peripheral blood in vivo. Blood samples of patients with indicated radiotherapy (RT) undergoing partial body irradiation (PBI) were obtained soon before the first treatment and then aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
(47 reference statements)
1
35
0
1
Order By: Relevance
“…Intratumoral MN showed a 5.4-fold increase after RT for 10 Gy in 5 fractions compared with pre-treatment setting. The increase in MN after irradiation was comparable with that reported previously in peripheral blood lymphocytes [ 12 , 13 , 14 , 15 ]. The novelty of this study is that, for the first time, we demonstrated the induction of MN in primary tumors treated with clinical radiation beams.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Intratumoral MN showed a 5.4-fold increase after RT for 10 Gy in 5 fractions compared with pre-treatment setting. The increase in MN after irradiation was comparable with that reported previously in peripheral blood lymphocytes [ 12 , 13 , 14 , 15 ]. The novelty of this study is that, for the first time, we demonstrated the induction of MN in primary tumors treated with clinical radiation beams.…”
Section: Discussionsupporting
confidence: 91%
“…Taken together, RT-induced intratumoral MN may be used as a biomarker of the response to cancer immunotherapy combined with radiotherapy. Induction of MN by RT has been demonstrated in peripheral blood lymphocytes obtained from individuals treated with RT [ 12 , 13 , 14 , 15 ]. However, the induction of MN by RT in solid tumors has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples from a previous study (13,36) were analyzed to monitor the radiation response in vivo of apolipoprotein B mRNA editing enzyme catalytic subunit 3H (APOBEC3H) and FDXR. This cohort was comprised of patients with the following cancer diagnoses (n): endometrial (4), breast (5), lung (4), prostate (3), esophageal (2) and colon (1). Patients received intensity modulated radiotherapy using a linear accelerator.…”
Section: Radiotherapy Patient Samplesmentioning
confidence: 99%
“…Over the last decade, gene expression analysis has emerged as a realistic approach for assessing radiation exposure in human blood samples after medical exposure or during emergency situations, due to its high throughput and time efficiency (1)(2)(3)(4). Although many studies have used microarrays (5,6), qPCR analyses have proven to provide accurate dose estimates by focusing on specific radiationresponsive genes (7)(8)(9)(10)(11)(12)(13)(14)(15) in only 7 h (16) and now in only 4 h (17).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression analyses of white blood cells have proven to be an accurate and fast method to assess IR exposure in blood samples for biodosimetry purposes [8][9][10][11][12][13][14]. From arrays and sequencing efforts [14][15][16], a broad number of genes have been identified whose response to IR can qualify as reliable biomarkers of exposure.…”
Section: Introductionmentioning
confidence: 99%